INNOVATIVE STRATEGIES IN SOCIAL STUDIES LEARNING TO INCREASE ELEMENTARY STUDENTS INTEREST IN LEARNING - Nora Sara Damayanti; Dyah Ayu Puspitaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Social Studies learning in elementary schools plays an important role in shaping students’ knowledge, social skills, and character from an early age. However, in practice, various challenges are still encountered that contribute to low student interest and learning outcomes, such as the dominance of lecture-based teaching methods, the lack of engaging learning media, and limited innovation in instructional strategies. This study aims to examine innovative learning strategies that can be applied in Social Studies instruction to enhance elementary students’ interest in learning. The method employed is a qualitative approach using a literature review, conducted through an analysis of various relevant journals and scientific articles. The findings indicate that the implementation of innovative strategies such as the Joyful Learning model, Team Quiz, the use of visual media, digital interactive media, learning applications such as Canva, and outdoor study methods can create a more engaging, participatory, and meaningful learning environment. These strategies have been shown to be effective in increasing students’ learning interest, active participation, as well as their critical and social thinking skills. The challenges faced by teachers in implementing these strategies include limited understanding of innovative models, limited availability of learning media, and time management constraints. Therefore, continuous teacher training and support from schools are necessary to ensure that innovative learning strategies can be optimally implemented in Social Studies learning at the elementary school level.